Confirmatory factor analysis of the wisdom scale according to the more model among university students - Elballah, Khaled Awad; Gaber, Sherif Adel; Hegazy, Ahmed Zakaria; Shahat, Hussein Ahmed (International Journal of Innovative Research and Scientific Studies, 2025)
Wisdom is one of the well-known concepts used in the field of positive psychology, and the concept was developed from multiple points of view, such as the Berlin model, Brown model, Ardelt model, Sternberg model, the MORE model, and HERO (E) Model. The current study aimed to prepare a scale of the components of wisdom development (CWDS) according to the MORE life experience model, which focused on five dimensions including mastery, openness, reflection, self-regulation, and empathy. Additionally, the estimates of the confirmatory factor analysis (CFA) and internal consistency were explored using Cronbach’s Alpha. A sample of 695 university students at King Faisal University was used. The results showed a good fit of the model to the data, with excellent indicators. These values indicate that the proposed model for the wisdom scale agrees with the data and that the scale is factorially valid. The findings of the CFA, which included defining the model and utilizing fit indicators, suggested that the model was appropriate for the field data and confirmed the structure of four factors for the scale, which were MA, measured with 5 items, RE, measured with 3 items, EM, measured with 7 items, and OP, measured with 3 items. The findings supported the psychometric properties of validity.